Packaging Information Cues and Willingness to Pay Premium for Private-Label Functional Foods: The Mediating Role of Brand Attachment - Anwar, Muhammad Usama; Abrar, Muhammad; Kiran, Faiqa (Journal of Development and Social Sciences, 2025)
This study seeks to investigate the influence of packing information cues on willingness to pay premium price, in private label function food context, and the mediating role of brand attachment. Packaging information cues are an important part of the consumer decision-making process. Understanding the relationship between these cues and consumer willingness to pay premium prices is crucial to retailers who want to position themselves competitively while the mediating role of brand attachment in this relationship has been under-explored in the functional food context. The study used a cross-sectional quantitative approach using data gathered from 384 consumers of private-label functional foods using a fully-structured questionnaire. The sample population was composed of consumers frequently purchasing private-label functional food products. Date analysis was performed using partial least squares-structural equation modelling (PLS-SEM) by Smart PLS software. The authors concluded that packaging information cues have important implications for consumers’ willingness to pay a premium price for private-label functional foods. Brand attachment was found to partially mediate the relationship demonstrating that not only did packaging information cues directly influence price premium willingness, but they worked indirectly by building greater brand attachment. These results highlight the dual pathway through which packaging information influence consumer purchasing behavior in functional food market. It is recommended that retailers use their packaging strategy to keep their own brands competitive. Future research should examine the effectiveness of specific elements of packaging information for functional foods to identify whether certain health benefits or nutritional claims are more effective to trigger consumer responses than others.